Consecutive yearly outbreaks of respiratory syncytial virus in a haemato-oncology ward and efficacy of infection control measures. Issue 4 (August 2017) - Inkster, T.; Ferguson, K.; Edwardson, A.; Gunson, R.; Soutar, R.
Summary: Background: Respiratory syncytial virus (RSV) causes significant respiratory tract infection in immunosuppressed patients. Aim: To describe two consecutive yearly outbreaks of RSV in our haemato-oncology ward. Methods: Haematology patients presenting with respiratory symptoms were screened by polymerase chain reaction for viral respiratory pathogens using a saline gargle. Findings: None of our patients had undergone bone marrow transplant but all had underlying haematological malignancies. Eight patients were affected in the first outbreak (mortality rate: 37.5%) and 12 patients were affected in the second (mortality rate: 8.3%). Extensive infection control measures were implemented in both outbreaks and were successful in preventing further cross-transmission. Conclusion: There was significant learning from both outbreaks and actions implemented with the aim of reducing the likelihood and impact of future outbreaks.